1990
DOI: 10.1007/bf00180299
|View full text |Cite
|
Sign up to set email alerts
|

Provisioning behavior and the estimation of investment ratios in a solitary bee, Calliopsis (Hypomacrotera) persimilis (Cockerell) (Hymenoptera: Andrenidae)

Abstract: One aspect of behavioral ecology that has received considerable attention, especially by students of social insects, is the relative amount of energy invested by parents in the rearing of male versus female offspring. Sexual selection theory makes predictions about how individuals should allocate their total investment in the sexes. To test these predictions we must accurately quantify the relative "cost" incurred by a parent in the production of an average individual of either sex. Body weight ratios are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 24 publications
3
61
0
Order By: Relevance
“…Pollen feeding was not restricted to day's end, as suggested for a few other ground-nesting solitary bees (Isenberg et al 1997;Danforth 1990Danforth , 1991. We found pollen masses in 36 % of the crops of nesting females caught after their first few foraging trips of the day and close to half of them by late morning (Figure 5a).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Pollen feeding was not restricted to day's end, as suggested for a few other ground-nesting solitary bees (Isenberg et al 1997;Danforth 1990Danforth , 1991. We found pollen masses in 36 % of the crops of nesting females caught after their first few foraging trips of the day and close to half of them by late morning (Figure 5a).…”
Section: Discussionsupporting
confidence: 80%
“…By evening, nearly all females had abundant pollen in both their crops and midguts, suggesting that they had eaten one recent pollen meal plus one (or more) meals earlier in the day. The few earlier studies, which only examined crop fill, reported just late-day Bfeeding tripsd uring nesting (Isenberg et al 1997;Danforth 1990Danforth , 1991. We found that female N. melanderi began gorging on pollen within hours of emergence and continued to eat daily pollen meals most, and possibly all, of their adult lives.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…There are positive correlations of mother size and brood cell size (Tepedino and Torchio 1989), mother size and amount of food supplied (Boomsma and Eickwort 1993), brood cell size and amount of food supplied (Krombein 1967, Johnson 1990), amount of food supplied and size of emergent bees (Klostermeyer et al 1973, Danforth 1990, Johnson 1990, and brood cell size and size of emergent bees (Klostermeyer et al 1973, Kamm 1974, Alcock 1979, Tepedino and Torchio 1982. In Lasioglossum zephyrum bee size is correlated with brood cell size: the larger bees construct larger cells and larger bees emerge from larger cells (Kamm 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the nests have between 6 and 15 cells and construction time varies from 3 to 6 weeks (Alves dos Santos et al 2002). As obvious as it may seem few studies have analyzed the amount of food for the larvae and size of emerged bees (Klostermeyer et al 1973, Danforth 1990, Johnson 1990). However, in none of them was removed food from brood cells.…”
Section: Introductionmentioning
confidence: 99%